Environmental salinity differentially impacts branchial and hepatic carbohydrate metabolism in tilapia - Ryan J. A. Chang; Fritzie T. Celino‐Brady; Jason P. Breves; Andre P. Seale (Journal of Fish Biology, 2025)
In response to changes in environmental salinity, euryhaline fishes mobilize energy to support the active transport of ions across osmoregulatory epithelia. Glycogen synthase (GS) and glycogen phosphorylase (GP) are key controllers of carbohydrate metabolism due to their roles in promoting glycogenesis and glycogenolysis, respectively. However, the coordinated responses of GS, GP and glucose transporters (GLUTs) in the liver and gill to changes in salinity remain unresolved. In this study, we initially subjected Mozambique tilapia ( Oreochromis mossambicus ) to unidirectional transfers, either from fresh water (FW) to seawater (SW) or from SW to FW. We then transferred FW‐ and SW‐acclimated tilapia to a tidal regime (TR) where salinity alternated between FW and SW every 6 h. Our goal was to characterize how carbohydrate metabolism is affected by unidirectional and tidal changes in salinity. Whether fish were transferred from SW to FW in a unidirectional manner or to a TR, glucose levels increased after transfer to FW or during the FW phase of the TR (TF). Conversely, hepatic glycogen levels were higher in fish in SW and the SW phase of the TR (TS) than in TF. In both FW and TF, branchial expression of the gill‐specific isoform of GP ( gpg ) was downregulated, while gs was upregulated. Branchial gpg was upregulated in fish unidirectionally transferred from FW to SW or sampled during TS. Hepatic gp and gs expression increased following transfer from SW to FW. Thus, we consistently found that increases in salinity promoted branchial glycogen breakdown, while decreases in salinity led to hyperglycaemia. Moreover, while branchial glucose transporter 1 ( glut 1 ) expression was downregulated after transfer from FW to SW, glut1 was transiently upregulated in the liver. In both liver and gill, glut1 expression was higher in fish in TF compared to TS. Gill filament explants incubated with cortisol exhibited reduced glut1 expression regardless of medium osmolality. Our collective data indicate that salinity differentially regulates hepatic and branchial carbohydrate metabolism.